Intuitional Branding Strategy to Strengthen Followers of the GenZi Study at Al Akbar Mosque Surabaya - Hanifah, Najmy; Fauji, Imam (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2025)
This study aims to analyze the institutional branding strategy implemented by the Gen Z study community at the Al Akbar Mosque in Surabaya in strengthening the involvement and loyalty of the younger generation to mosque-based da'wah activities. The study uses a qualitative method with a case study approach to explore how the Gen Z community utilizes social media, the selection of popular sources, and institutional support from the Al Akbar Mosque in forming a positive and relevant image for young audiences. The results of the study show that Brand Identity is realized through the use of the Al Akbar Mosque logo, digital pamphlets, and consistent visual documentation on Instagram, creating a strong association with the image of the mosque as a modern da'wah institution. Brand Personality and Brand Association are strengthened by the presence of popular sources, such as Ustadz Hanan Attaki, who are relevant to the younger generation and increase the appeal of the study. In addition, Brand Benefit and Competence are reflected in the unique experiences offered, such as the implementation of the study at dawn, which creates a deep spiritual experience. A consistent institutional branding strategy, including communication through Instagram and WhatsApp groups, builds a responsive Brand Attitude and Behavior and supports the active involvement of young congregants. This study concludes that planned and consistent institutional branding is able to build strong emotional relationships and loyalty of the younger generation to the da'wah community. This strategy is an effective model in the context of digital da'wah and can be adapted by other mosques to build relevant and sustainable relationships in the digital era.